The Use of Tahfiz Learning Methods as Extracurricular at Madrasah Tsanawiyah Negeri 8 Padang Pariaman - Hirawan, Robi (Ruhama : Islamic Education Journal, 2025)
The global decline in Quranic memorization (Tahfiz) engagement among youth, driven by modern distractions and shifting educational priorities, poses a significant challenge to preserving Islamic heritage. This study addresses this issue by examining the methods of Tahfiz learning as an extracurricular activity at MTsN 8 Padang Pariaman, aiming to identify effective strategies for enhancing students' memorization. Using a qualitative approach, data were collected through interviews, observations, and documentation involving the school principal, Tahfiz teachers, and students. The findings reveal that a combination of traditional methods (e.g., Tahsin, Talqin) and modern techniques (e.g., Tasmi’, Talaqqi) effectively supports memorization. Students benefit from independent and peer-assisted learning, while structured schedules and motivational support from teachers and parents play a crucial role. However, challenges such as time constraints, lack of focus, and inconsistent routines hinder optimal outcomes. The study concludes that addressing these challenges through structured schedules, peer tutoring, and parental engagement can significantly improve memorization outcomes. Despite its contributions, this research is limited by its focus on a single institution, which may affect the generalizability of the findings. Future studies should explore diverse educational contexts and incorporate longitudinal designs to assess the long-term impact of Tahfiz programs. This study underscores the importance of innovative and holistic approaches to Tahfiz education in addressing global challenges and preserving Quranic memorization traditions.